Cuestiones indígenas Sateré-Mawé (AM) a partir de una mirada folkcomunicacional (Revista Internacional de Folkcomunicação, 2019)
The paper highlights questions related to the Sateré-Mawé (food, tuxaua and çapó) and their sociocultural meanings for that people, using folkcommunication theory to demonstrate that knowing and doing are not only a symbolic way of perpetuating beliefs and traditions of the nation, as they also represent communicational links of relations between traditional leaders, community and non-indigenous society. Folkcommunicational evidences were observed according to studies by Beltrão (1980, 2001, 2004), Lorenz (1992) and Souza (2014), which constituted the methodological corpus of the research. Sateré-Mawé; Folkcomunicação; Guarana; Hood.